Spectroscopic Measurements of Impurities in The Plasma Stream (I) - Tanaka, Masatoshi; Inoue, Kenji; Mori, Sigeru (Kakuyūgō kenkyū, 1965)
The plasma stream presented by our coaxial plasma gun includes various impurity components of which copper and carbon are very serious. Emission lines from these impurities are measured by a 3. 4M Fastie-Ebert type polychrometor. In order to reduce copper ions, a longitudinal magnetic field is applied along, the passage of the plasma stream. For example, relative intensity of CuII 2247A to HeII 4686A is redu ced to 1/30 after passing through a magnetic field of 1000 gauss. Also, this relative intensity varies with operation conditions of the gun.